2020
DOI: 10.1164/rccm.202003-0817le
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Does Not Lead to a “Typical” Acute Respiratory Distress Syndrome

Abstract: An intermediate VT (7-8 ml/kg PBW) ventilation strategy was applied to the first four patients to increase pulmonary efficiency to eliminate CO 2 , and this was used in the next four patients. Gas exchange consists of oxygenation and ventilation. Oxygenation is quantified by the Pa O 2 /FI O 2 ratio, and this method has gained wide acceptance, particularly since publication of the Berlin definition of ARDS (7). However, the Berlin definition does not include additional pathophysiological information about ARDS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

59
1,412
8
95

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 1,281 publications
(1,574 citation statements)
references
References 3 publications
59
1,412
8
95
Order By: Relevance
“…In contrast with reports from China or Seattle suggesting a severe ARDS, a strategy of early intubation disclosed that SARS-CoV-2 does not lead to a typical ARDS. In our experience, two thirds of our patients have initial lung compliance > 40 ml/cm H20 postintubation being consistent with a preliminary report with 16 patients by Gattinoni et al (6), suggesting that ARDS is a consequence of acute lung injury associated with delayed intubation or super-infection.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In contrast with reports from China or Seattle suggesting a severe ARDS, a strategy of early intubation disclosed that SARS-CoV-2 does not lead to a typical ARDS. In our experience, two thirds of our patients have initial lung compliance > 40 ml/cm H20 postintubation being consistent with a preliminary report with 16 patients by Gattinoni et al (6), suggesting that ARDS is a consequence of acute lung injury associated with delayed intubation or super-infection.…”
Section: Discussionsupporting
confidence: 92%
“…Although more information on procalcitonin is required [12], our findings suggest that no prognostic information can be inferred. This early report of characteristics of SARS-CoV-2 influenza in Spain is of interest, as most information currently available is coming from large cohorts in China, or short case series from Italy or USA (5,6,11,13) . An important characteristic is that in the current cohort, no patients were exposed to prior non-invasive ventilation, which was commonly performed using a facial mask in Wuhan or a helmet in Italy, with a protocol of earlier intubation based on hyperventilation unable to maintain Satv02 above 90%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 The improvement in oxygenation noted with increased PEEP in COVID-19 "ARDS" may be attributable to decreased cardiac output, leading to decreased shunt fraction rather than to alveolar recruitment. 1 Autopsy studies from the SARS outbreak of the early 2000s, caused by SARS-CoV-1 virus, have demonstrated pulmonary thrombi, pulmonary infarcts, and microthrombi in other organs. [5][6][7][8] It appears that SARS-CoV-2 is causing similar pathophysiological derangements.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%
“…While patients with COVID-19 respiratory failure may fulfill the Berlin criteria for acute respiratory distress syndrome (ARDS), their syndrome is atypical in that they have relatively well-preserved lung mechanics. 1 The marked dissociation between pulmonary mechanics and gas exchange raises the possibility of pulmonary vascular involvement.…”
Section: Introductionmentioning
confidence: 99%